Defence against terrorism - Duyan, Adil; Kibaroglu, Mustafa (NATO science for peace and security series. E, Human and societal dynamics, 2011)
This book presents the lectures delivered at the NATO Advanced Training Course (ATC) ''Defence Against Terrorism'', held in Amman, Jordan, in January 2010. The purpose of this course, which brought together academics, experts on terrorism and interested parties from NATO countries, was to support NATO on defence issues related to terrorism. Following an introductory chapter which provides a general framework for understanding the history and causes of terrorism, the chapters which follow present a brief overview of alliance antiterrorism operations and their objectives; media and communications; weapons of mass destruction and the opportunities terrorists may have for obtaining them; combating the financing of terrorism post9/11; relationships between organized criminals and terrorists and lastly, the role and place of strategic communications in combating terrorism. The final chapter discusses future trends in terrorism by looking at the changing profile of terrorism with regard to ideology, organization and structure as well as the means and methods used by terrorists. The collection of these articles in book form covers many different perspectives on terrorism and helps to create an awareness of this growing problem, offering further factors for consideration in the improvement of defense against terrorism and response to related risks. This is a subject of interest not only to those directly involved in this field, but also to a wider audience.